Behaviour of a friction connection using TCB in long slotted holes - Husson, Wylliam; Veljkovic, Milan (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2007)
With constantly increasing demand for renewable energies the cost optimization of steel towers supporting multi-mega-watt wind turbines becomes important. Luleå University of Technology currently coordinate European research project (RFCS), including partners from 5 countries, which aim is to ensure the high competitiveness of the next generation of steel towers produced in Europe. One innovation investigated within this project is the use of friction grip connection with long slotted holes to connect the steel tower sections. This paper presents a part of ongoing experimental program and result of three segment tests performed with weathering steel plates and M20 Tension Control Bolts. Experimental results are compared to the prediction according to European structural code EN 1993-1-8 Furthermore a three dimensional numerical model was used to describe behaviour of the connection with a long slotted hole together and a thick cover plate FE-analysis of the preliminary experiments was used to endorse conclusions from the experiments. Godkänd; 2007; 20071010 (ysko)